Drugging the undruggable: activity-based protein profiling offers opportunities for targeting the KLK activome - Lee, Kristi Y.; Chau, Cindy H.; Price, Douglas K.; Figg, William D. (Cancer biology & therapy, 2022)
The vast majority of the human proteome is yet to be functionally characterized thus hindering ongoing investigations on potential drug resistance mechanisms and advanced treatment options. Chemical proteomics is a powerful solution for enzyme profiling and the development of next generation cancer therapeutics previously deemed undruggable by small molecules. Within this field, activity-based protein profiling (ABPP) is a specialized technology capable of discriminating enzyme interactions that occur within complex, biological environments. In a recent publication by Lovell et al, the kallikrein-related peptidase (KLK) family of serine proteases that is highly implicated in the progression of prostate cancer (PCa) was subject to ABPP to elucidate enzymatic activities in the presence of enzalutamide. This is the first report of ABPP in PCa and of activity-based chemical probes selective for individual KLKs. Further, the study reveals androgen receptor-dependent activity among KLK proteins, particularly in mediating the invasion of the bone microenvironment.